Robotic Dispersal Technique for 35 GBq of 140La in an L-polygon Pattern. Issue 4 (April 2020) - Beckman, Blake; Green, Anna Rae; Sinclair, Laurel; Fairbrother, Blaine; Munsie, Tim; White, Dan
Abstract : Abstract: In 2018, Defence Research and Development Canada, in partnership with Natural Resources Canada, led a field trial of survey and mapping of a large dispersion of radioactivity using Unmanned Aerial Vehicles (UAVs). The intent was to disperse 140 La material in a 3, 200 m 2 L-polygon with an approximate activity level of 10 MBq m −2 and to measure the radioactive material using sensors carried by UAVs. Due to the potential radiological hazard to personnel, the activity was approved only if Unmanned Ground Vehicles (UGVs) were able to completely handle and disperse the material remotely. One UGV was equipped with a traditional agricultural sprayer to disperse the material, and one UGV was equipped with a force feedback manipulator arm. Due to the freezing temperatures during dispersal, the 35 GBq of 140 La was dispersed non-uniformly as one sprayer boom failed to perform as tested. However, rough analysis of the electronic dosimetry on the UGV concluded that 99% of the material was dispersed on the ground. The dosimeter placed closest to the robot manipulator arm, used for dispersal of material, indicated a contact dose of 33.5 mSv. The electronic dosimeter placed where the driver would have sat on the sprayer vehicle if it were not unmanned indicated a dose of 22.3 mSv. Thus, the use of UGVs for material dispersion substantially reduced the external exposure to personnel. The use of UGVs eliminated the potential of internal exposure as well. The Radiation Safety Officer received the highest dose at approximately 3 μSv, with the majority of the exposure coming from the handling of the Type A container.